Including a symposium on Latin American monetary thought : two centuries in search of originality - Fiorito, Luca, 1967-; Scheall, Scott; Suprinyak, Carlos Eduardo (Research in the history of economic thought and methodology, 2018)
Volume 36C of Research in the History of Economic Thought and Methodology features a symposium edited by Andrés Álvarez on monetary economics in post-independence Latin America. The symposium features contributions from Matías Vernengo and Esteban Pérez Caldentey, Ricardo Solis Rosales, Florencia Sember, and Edna Carolina Sastoque Ramírez. Volume 36C also includes general research contributions from C. Tyler Des Roches and Dorian Jullien.